Leadership and teamwork in medical emergencies: performance of nursing students and registered nurses in simulated patient scenarios. Issue 1 (4th June 2014) - Endacott, Ruth; Bogossian, Fiona E; Cooper, Simon J; Forbes, Helen; Kain, Victoria J; Young, Susan C.; Porter, Joanne E; the First2Act Team
<x xml:space="preserve">Abstract</x> Aims and objectives To examine nursing students' and registered nurses' teamwork skills whilst managing simulated deteriorating patients. Background Studies continue to show the lack of timely recognition of patient deterioration. Management of deteriorating patients can be influenced by education and experience. Design Mixed methods study conducted in two universities and a rural hospital in Victoria, and one university in Queensland, Australia. Methods Three simulation scenarios (chest pain, hypovolaemic shock and respiratory distress) were completed in teams of three by 97 nursing students and 44 registered nurses, equating to a total of 32 student and 15 registered nurse teams. Data were obtained from (1) Objective Structured Clinical Examination rating to assess performance; (2) Team Emergency Assessment Measure scores to assess teamwork; (3) simulation video footage; (4) reflective interview during participants' review of video footage. Qualitative thematic analysis of video and interview data was undertaken. Results Objective structured clinical examination performance was similar across registered nurses and students (mean 54% and 49%); however, Team Emergency Assessment Measure scores differed significantly between the two groups (57% vs 38%, t = 6·841, p < 0·01). In both groups, there was a correlation between technical (Objective Structured Clinical Examination) and nontechnical (Team Emergency Assessment Measure) scores for the respiratory distress scenario (student teams: r = 0·530, p = 0·004, registered nurse teams r = 0·903, p < 0·01) and hypovolaemia scenario (student teams: r = 0·534, p = 0·02, registered nurse teams: r = 0·535, p = 0·049). Themes generated from the analysis of the combined quantitative and qualitative data were as follows: (1) leadership and followership behaviours; (2) help‐seeking behaviours; (3) reliance on previous experience; (4) fixation on a single detail; and (5) team support. Conclusions There is scope to improve leadership, team work and task management skills for registered nurses and nursing students. Simulation appears to be beneficial in enabling less experienced staff to assess their teamwork skills. Relevance to clinical practice There is a need to encourage less experienced staff to become leaders and for all staff to develop improved teamwork skills for medical emergencies.